Efeito da posição do grão na espiga sobre as porcentagens de proteína e lisina no milho (Zea mays L.) opaco-2 - Saraiva, Luiz Sérgio; de Almeida Filho, José (Revista Ceres, 2025)
Percent protein, lysine and lysine/protein ratio were studied as a function of kernel position on ears of opaque-2 corn. There was no consistent relationship between kernel posi- tion and percent protein, lysine or lysine as percent of pro- tein for opaque-2 hybrid, variety and inbreds.